2007
DOI: 10.1186/1751-0147-49-19
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic closure time of appendicular growth plates in the Icelandic horse

Abstract: Background: The Icelandic horse is a pristine breed of horse which has a pure gene pool established more than a thousand years ago, and is approximately the same size as living and extinct wild breeds of horses. This study was performed to compare the length of the skeletal growth period of the "primitive" Icelandic horse relative to that reported for large horse breeds developed over the recent centuries. This information would provide practical guidance to owners and veterinarians as to when the skeleton is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 21 publications
3
32
0
Order By: Relevance
“…Since there is a possibility that some lesions are caused by a different mechanism, it is appropriate to investigate lesions from sites related to growth plates that are still active, with the proviso that no gross signs of secondary changes are present. This is the approach taken for the specimens used in the immunohistochemical studies presented here; the specimens (distal ends of femur and tibia) were taken several months before the expected closure of the associated growth plates . The specimens from the feeding trial were from sites (glenoid of the scapula and cervical vertebrae) for which specific growth plate closure data are not available, however, these bones continue to grow significantly in the second year of life .…”
Section: Discussionmentioning
confidence: 99%
“…Since there is a possibility that some lesions are caused by a different mechanism, it is appropriate to investigate lesions from sites related to growth plates that are still active, with the proviso that no gross signs of secondary changes are present. This is the approach taken for the specimens used in the immunohistochemical studies presented here; the specimens (distal ends of femur and tibia) were taken several months before the expected closure of the associated growth plates . The specimens from the feeding trial were from sites (glenoid of the scapula and cervical vertebrae) for which specific growth plate closure data are not available, however, these bones continue to grow significantly in the second year of life .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in horses showed that there are no differences between the front foot and hind foot (Crevier et al, 1994a), but this was not evaluated in this study on the donkey. It is interesting that based on the results of this study, the radiographic closure times of the growth plates of the distal extremity of the manus in the donkey distal limb are considerably later than those published for the horse (Butler et al, 2008;Crevier et al, 1994a,b;Smallwood et al, 1989Smallwood et al, , 1990Strand et al, 2007). However, it has been described previously that closure times can be breed dependent (Butler et al, 2008;Crevier et al, 1994a,b;Smallwood et al, 1989Smallwood et al, , 1990Strand et al, 2007).…”
Section: Discussionmentioning
confidence: 50%
“…It is interesting that based on the results of this study, the radiographic closure times of the growth plates of the distal extremity of the manus in the donkey distal limb are considerably later than those published for the horse (Butler et al, 2008;Crevier et al, 1994a,b;Smallwood et al, 1989Smallwood et al, , 1990Strand et al, 2007). However, it has been described previously that closure times can be breed dependent (Butler et al, 2008;Crevier et al, 1994a,b;Smallwood et al, 1989Smallwood et al, , 1990Strand et al, 2007). A higher rate of growth in horses with larger body dimensions is also been observed (Ruohoniemi, Laukkanen, Ojala, Kangasniemi, & Tulamo, 1997 Thoroughbred horses (Empel, Lojek, & Wasowski, 1993;Vulcano, Mamprim, Muniz, Moreira, & Luna, 1997).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Radiographic closure time for the distal femoral physis is reported as 19–27 months of age, while the proximal tibial physis closure occurs from 23 to 32 months of age (Strand et al . ). While that particular study was performed in Icelandic horses, overall closure times correlated well with reports from other breeds at other physes.…”
Section: The Complexity Of Physeal Fracturesmentioning
confidence: 97%